2012
DOI: 10.5897/ijbc11.187
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of sacred fir (Abies religiosa) in the Nevado de Toluca National Park

Abstract: , are threatened principally by illegal cutting and an increasing incidence of parasites as bark beetles and dwarf mistletoe. An important and sometimes ignored component of conservations plan is genetic variability hence, it is necessary to carry out studies on the genetic diversity of sacred fir to create an efficient plan of conservation and management. In the present study DNA markers were used to analyze genetic variability of seventeen populations of sacred fir. Results suggest high values of genetic var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Estas forman poblaciones y comunidades forestales altamente diversas (INEGI, 2010;Astudillo et al, 2017) contribuyendo así a la existencia de abundante variabilidad genética de especies de animales y plantas. Pinus hartwegii en particular posee bajos niveles de diversidad genética que podrían contribuir al ataque de descortezadores (Heredia-Bobadilla et al, 2012;Heredia-Bobadilla et al, 2016;Sunny et al, 2019). Sin embargo, a pesar de tratarse de dos ANPs, el deterioro en ambas regiones es constante, siendo la tala clandestina, el cambio de uso de suelo, la sobreexplotación de los mantos hídricos y los incendios forestales las perturbaciones antrópicas más comunes (Arriola-Padilla et al, 2015).…”
Section: Materiales Y Métodosunclassified
“…Estas forman poblaciones y comunidades forestales altamente diversas (INEGI, 2010;Astudillo et al, 2017) contribuyendo así a la existencia de abundante variabilidad genética de especies de animales y plantas. Pinus hartwegii en particular posee bajos niveles de diversidad genética que podrían contribuir al ataque de descortezadores (Heredia-Bobadilla et al, 2012;Heredia-Bobadilla et al, 2016;Sunny et al, 2019). Sin embargo, a pesar de tratarse de dos ANPs, el deterioro en ambas regiones es constante, siendo la tala clandestina, el cambio de uso de suelo, la sobreexplotación de los mantos hídricos y los incendios forestales las perturbaciones antrópicas más comunes (Arriola-Padilla et al, 2015).…”
Section: Materiales Y Métodosunclassified
“…For example, Aguirre-Planter et al (2000) identified a relationship between gene flow and geographic distances in TVB populations based on isoenzymes. Heredia-Bobadilla et al (2012) reported a high genetic variability between populations and low levels of gene flow in populations inhabiting the Nevado de Toluca National Park, using chloroplast DNA (cpDNA; cp-trnK, cp-TRNG-trnQ) and mitochondrial DNA (mtDNA; nad-5, coz3in). Also, Jaramillo-Correa et al (2008), through mtDNA and cpDNA, revealed that the Mesoamerican Abies species share a recent common ancestor and that their divergence and speciation have been determined mainly by genetic drift and isolation during warm interglacial periods.…”
Section: Introductionmentioning
confidence: 99%
“…The TMVB region encloses a large number of natural protected areas (NPA), the Protection of Flora and Fauna Area Nevado de Toluca (PFFANT) is one of them. The closeness of this NPA to large cities entails environmental pressures that includes the presence of human settlements, illegal logging, introduction of exotic species and the growing incidence of forest parasites like bark beetles and dwarf mistletoes [1][2][3].…”
Section: Introductionmentioning
confidence: 99%